Comics and reading literacy: for a teaching practice of the sequential art - Vincenzo Beccia; Serafina Pastore (Firenze University Press, 2017)
Is it possible to use comics at school in order to further students' reading literacy? In this article the authors try to reply to this question applying the principles of the sequential art. Moving from the robust consensus of educational value of images in textbooks, the proposal of a mediation realized using multimodal texts, like comics, represents an alternative and valid solution to traditional teaching reading paths. After a literature review, an analysis of implications and main criticalities on using comics at school is presented. These passages are functional to explore new didactic scenarios where images and written texts can be used to promote the development of the reading literacy as an interactive and social activity.   Fumetti e competenza di lettura: per una didattica dell'arte sequenziale È possibile utilizzare il fumetto a scuola per la promozione della competenza di lettura? Il presente articolo prova a rispondere a questa domanda ricorrendo ai principi dell'arte sequenziale. A fronte del riconoscimento, ormai consolidato, del valore educativo delle immagini nei libri, la proposta di una mediazione realizzata attraverso testi multimodali, quali quelli del fumetto, si pone come un'alternativa didattica ai tradizionali percorsi di insegnamento-apprendimento della lettura. Alla rassegna sul fumetto è affiancata così una disamina delle implicazioni e delle criticità correlate al suo uso a scuola: passaggi funzionali all'esplorazione dei possibili scenari di una didattica che, puntando su immagini e parola scritta, consenta di promuovere l'acquisizione e lo sviluppo della competenza di lettura intesa come attività sociale e interattiva.